Computer-Based Documentation Increase Efficiency and Quality of Nursing Care - Mila; Tri Kurniati; Giri Widakdo (NERS Jurnal Keperawatan, 2025)
Nursing documentation is a crucial aspect of nursing practice, yet manual documentation systems often encounter barriers that may impact care quality. This study aims to examine the association between the use of computer-based documentation systems and perceived work efficiency and quality of nursing care among nurses at a national referral hospital in Jakarta. A cross-sectional quantitative study was conducted in November 2024 involving all 178 inpatient nurses at a national referral hospital in Jakarta using total sampling. The study included nurses working in inpatient units that had implemented computer-based documentation and who consented to participate. Of the 178 respondents, primarily aged 24–34 years (58%) and female (88%), 61% reported not yet using computer-based documentation. Analysis showed a statistically significant association between the use of computer-based documentation and both work efficiency (OR 53.167) and perceived quality of nursing care (OR 22.733) (p < 0.05). Findings suggest that the use of computer-based documentation is associated with higher perceived efficiency and quality in nursing care. These associations may be attributed to reduced time spent on manual documentation, enhanced communication among healthcare providers, and improved safety measures. Further research using longitudinal or interventional designs is needed to explore causal relationships.